A Journey through survival, pain and hope an interpretative phenomenological analysis of the street children phenomenon. - Villacorta, Tesha Mae M
The street children phenomenon has been a growing problem faced by urban societies. This social issue has been attributed to community and personal factors that have pushed the child into the streets. Thus, they have been considered to be at risk to the culture of violence and unequal access to resources leaving them experts of their own experiences of struggle and survival. Therefore, this study focuses on exploring the lived experiences of street children through Interpretative Phenomenological Analysis (IPA) as a lens. Six sheltered street children from the Crisis Intervention Unit of Department of Social Welfare and Development were interviewed and findings revealed that children encounter experiences of stigmatization and discrimination, violence and abuse, and also care and security. With their experiences, they have learned to deal with these harsh realities through fleeing from the risk, fighting back, seeking and preserving their own support system, accepting the blame, and creating long-term goals and having good values. Furthermore, their experiences are mostly characterized by violence in which violence is either direct or structural. Because of violence, as well, males are able to establish their own autonomy but for females, violence has overshadowed the presence of ?family hood? within the group. Hence, this study served as an avenue for breaking the silence of street children and recommends that research focusing on this phenomenon and using IPA as a lens should be extended.